Trematode larvae in Lymnaea rubiginosa and their definitive host in irrigated rice fields in West Java - Estuningsih, S.E.; Copeman, D.B. (Indonesian Animal Sciences Society, 1995)
The aim of this study was to identify trematodes which utilise Lymnaea rubiginosa as the fast intermediate host. This study was conducted in irrigated rice fields in Bogor regency and at Surade, West Java. A total of 3,253 L rubiginosa were collected from irrigated rice fields from Bogor regency and 2,875 from Surade. The results showed that cercariae of echinostomes, strigeid, Trichobilharzia sp. and Xiphidiocercariae were found in snails from Bogor regency, whereas Xiphidiocereariae and cereariae of Fasciola gigantica, Schistosoma sp . and echinostomes were found in snails from Surade . The larval echinostomes found in L. rubiginosa and adult echinostomes in domestic ducks and village chickens which grazed harvested rice fields in Bogor regency were both identified as Echinostoma revolution. The adult echinostomes were not found in the 24 rats, 11 lizards and 35 frogs caught in the vicinity of the Bogor regency . The possible sources of strigeids, Trichobilharzia and Xiphidiocercariae are discussed . Key words: Fasciola gigantica, trematode, larvae, Lymnaea rubiginosa